Psychological contract breach as a stressor in the physician’s job commitment–extra-role behaviour relationship - Koomson, Samuel (Journal of Psychological Perspective, 2021)
This paper finds out if a committed physician will go the extra mile for his/her employer when faced with psychological contract breach (PCB), a psychosocial stressor. Data from 214 physicians across 26 health-care units in the Upper East (UE) and Upper West (UW) regions of Ghana were analysed. A semi-structured, pre-tested and validated questionnaire was utilised. Research philosophy was positivism, research approach was quantitative, research design was explanatory, and study design was cross-sectional. Preliminary tests were conducted. Both reflective measurement and structural models were examined. PLS algorithm tool and bootstrapping procedure were used. Control variables were sex, age, employment type and tenure. A significant level was set at 5%. Smart PLS and IBM SPSS software were employed. In the end, physician’s commitment work (JCM) positively and significantly predicted extra-role behaviour (ETB). Also, PCB significantly interacted with JCM to predict ETB, such that the relationship between JCT and ETB was stronger when PCB was low than when it was high. Creating a balanced, fulfilled and harmonious hospital–physician relationship will transform the workplace into a less stressful, more meaningful and purposeful atmosphere for the benefit other health-care professionals, patients and the health-care organisation at large.